Watson–Crick base pairing in 9-methyladenine and ethylene-9, 9′-diadenine structures with close to 70% solvent content. Issue 34 (18th July 2016) - Qi, L.; Gundersen, L.-L.; Chamgordani, E. J.; Görbitz, C. H.
Abstract : 1, 1, 1, 3, 3, 3-Hexafluoro-2-propanol is an excellent solvent for molecules with nucleic acid components and has here been used to obtain highly solvated structures with uncommon hydrogen bonding patterns. Abstract : In small organic molecules with adenine (A) moieties the nucleobases usually form hydrogen-bonded AAA tapes with trans Watson–Crick/Hoogsteen base pairs. In the crystal structure of ethylene-9, 9′-diadenine tetra-1, 1, 1, 3, 3, 3-hexafluoro-2-propanol solvate presented here, the hydroxyl group of the co-crystallized solvent molecules replaces the adenine –NH2 group as donor for the attractive N7 acceptor, leading instead to a highly solvated structure with less common trans Watson–Crick/Watson–Crick base pairs. The properties of hexafluoro-2-propanol as a hydrogen bond pattern modifier was subsequently demonstrated by using it as a crystallization solvent for 9-methyladenine, yielding a structure with the same hydrogen bonds and solvent content as the diadenine analogue.